2019
DOI: 10.1371/journal.pone.0210408
|View full text |Cite
|
Sign up to set email alerts
|

Being HIV positive and staying on antiretroviral therapy in Africa: A qualitative systematic review and theoretical model

Abstract: BackgroundAdherence to antiretroviral therapy (ART) and long-term uninterrupted engagement in HIV care is difficult for HIV-positive people, and randomized trials of specific techniques to promote adherence often show small or negligible effects. Understanding what influences decision-making in HIV-positive people in Africa may help researchers and policy makers in the development of broader, more effective interventions and policies.MethodsWe used thematic synthesis and a grounded theory approach to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 127 publications
(437 reference statements)
6
92
0
Order By: Relevance
“…The frequency of ART visits was a significant stress and in their experience of 2-month refills, patients reported finding ways around their visits that did not jeopardise other obligations. Patients live in complicated worlds that require navigation of competing priorities, 22 and if a choice has to be made, life commitments may be prioritised at the expense of ART. Six-month refills helped to overcome this tension by reducing the impact of many previously described barriers to engagement with the health system, such as travel, stigma, inconvenience of appointments, changes to routine and being busy preventing attendance.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of ART visits was a significant stress and in their experience of 2-month refills, patients reported finding ways around their visits that did not jeopardise other obligations. Patients live in complicated worlds that require navigation of competing priorities, 22 and if a choice has to be made, life commitments may be prioritised at the expense of ART. Six-month refills helped to overcome this tension by reducing the impact of many previously described barriers to engagement with the health system, such as travel, stigma, inconvenience of appointments, changes to routine and being busy preventing attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showed that LTFU is associated with base line sociodemographic factors like sex [10,16,[22][23][24], age [10,11,13,25,26], educational status [26,27], marital status [25,28,29], occupation [30,31], disclosure status [16,27], distance from the health facility [29], caregiver [32,33] and clinical and treatment related factors like baseline WHO stage [25,34], baseline CD4 count [13,31,35], history of opportunistic infection at enrollment [10], baseline functional status [15,32,[35][36][37], opportunistic prophylaxis [11,13,14,29] and type of ART regimen at start of their medication [23,31].…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative systematic review of 59 studies regarding long-term ART adherence and engagement in care in Africa, poor clinical services were identified as a major theme, with long waiting times, inflexible services and rigid and demanding policies all leading clients to disengage from care. 14 In our study, CCMDD changed some of the 'materialities' of ART provision, leading to clear practical benefits for clients. Similar findings have been reported in qualitative assessments of community adherence clubs in Mozambique, Kenya, Malawi, Zimbabwe and South Africa, which found reductions in clinical visits, waiting times and transport costs for clients.…”
Section: Materialitiesmentioning
confidence: 70%